Geochronology of the Early Triassic based on coupled Bayesian zircon eruption age and Bayesian age–depth models - Xu Dai; Maria Ovtcharova; Joshua H. F. L. Davies; Huyue Song; Xiaokang Liu; Zhiwei Yuan; Yiran Cao; Ruoyu Bai; Daoliang Chu; Jacopo Dal Corso; Arnaud Brayard; Shouyi Jiang; et al. (Proceedings of the National Academy of Sciences, 2025)
Precise and accurate geochronology is essential for reconstructing Earth’s history and coeval life evolution. The Early Triassic was a critical time interval following the greatest Phanerozoic mass extinction, recording remarkable biotic changes and a series of environmental and climatic upheavals. Its geochronology remains, however, rather poorly constrained and highly debated. Here, we present high-precision zircon U-Pb dates for four ash beds from the Induan in South China, along with carbon isotope data. We use coupled Bayesian eruption age and Bayesian age–depth models to estimate the ages of our ash beds and to reinterpret the published ages of 25 ash beds from other four sections in South China, as well as to construct new age–depth models for each section. Our new age–depth models, integrated with biostratigraphic data, yield new age estimates for the following boundaries: Permian–Triassic (~251.867 Ma), Griesbachian–Dienerian (~251.562 Ma), Induan–Olenekian (~250.626 Ma), Smithian–Spathian (~249.236 Ma), and Olenekian–Anisian (~246.979 Ma). Calibration of the Early Triassic carbon isotopic record using the new age model reveals highly variable rates of individual carbon isotope excursions. For instance, the negative excursion across the Permian–Triassic boundary exhibits a rate of approximately −11.7‰ per 100 kyr—nearly seven times faster than the early Smithian negative excursion rate of approximately −1.7‰ per 100 kyr. This refined age model also provides a robust temporal framework to evaluate the tempo of biotic evolution in the aftermath of the Permian–Triassic mass extinction.